CMOS programmable P, PI, PD and PID controller circuit using CCTAs - Kumngern, Montree; Torteanchai, Usa (My University, 2016)
This paper presents a new programmable analog electronic proportional-integral-derivative controller circuit using current conveyor transconductance amplifiers as active elements. Unlike previous works, proportional controller, proportional-integral controller, proportional-derivative controller and proportional-integral-derivative controller of proposed structure can be programmed by the bias currents. Also proportional gain, integral time constant and derivative time constant can be electronically controlled. The use of grounded capacitor makes the proposed structure suitable for integrated circuit implementation. The simulation results are used to confirm the workability of the proposed circuit.
Keywords: current conveyor transconductance amplifier; digitally programmable circuit; PID controller